Penerapan Teknik Sinematografi oleh Director of Photography pada Video Feature “Ibu untuk Bumi” Bertema Gaya Hidup Berkelanjutan - Ikhwan Amar Mahesa; Toto Sugito; Andri Yanto (Pusat Riset dan Inovasi Nasional, 2025)
This final project aims to examine how cinematographic techniques are applied by the Director of Photography (DoP) to enhance the delivery of visual messages in the feature video